PERLINDUNGAN HUKUM TERHADAP PEKERJA AKIBAT PEMUTUSAN HUBUNGAN KERJA TANPA MENDAPATKAN KOMPENSASI BERDASARKAN UNDANG-UNDANG NOMOR 13 TAHUN 2003 (ANALISIS KASUS: PUTUSAN PENGADILAN PERSELISIHAN HUBUNGAN INDUSTRIAL NOMOR: 2/PDT.SUS-PHI/2019/PN SMR) - William Mulyadanika; Rasji Rasji (Fakultas Hukum Universitas Tarumanagara, 2021)
Termination of employment is one of the problems that often occurs in employment relations between workers / workers and entrepreneurs. The termination of an employment relationship for workers is a very complex problem because workers / laborers lose their livelihoods. One aspect of the cause of termination of employment is resignation, in which the resignation should be done voluntarily but in reality this resignation is carried out under pressure or coercion from the employer, and the employer manipulates workers so that they do not get their rights. So that resignation which should not be a dispute turns into a dispute that occurs. Bambang Trianto initially worked with one position then added a new position with the same wages so that Bambang Trianto wanted to resign, so that Bambang Trianto was terminated by PT. Hevilift Aviation Indonesia on charges of embezzlement of company money and selling hazardous and toxic waste belonging to the company without evidence of a criminal verdict so that he does not have strong evidence, so Bambang Trianto filed a lawsuit at the Industrial Relations Court at the Samarinda District Court, but in this verdict the rights workers' property to get severance pay or tenure rewards cannot be fulfilled. This study is normative in nature with literature study data collection techniques. Just like a scale that is used as a symbol of justice, the judge must also consider the fulfillment of workers 'property rights, so that in this case the workers' property rights can be fulfilled.